Post-disaster construction & demolition debris management: a Sri Lanka case study - Karunasena, Gayani; Amaratunga, Dilanthi; Haigh, Richard (Journal of Civil Engineering and Management, 2012)
The increasing nature of impacts from disasters has made post disaster management a key area of concern. The management of disaster waste is revealed as an area of least concern yet it presents momentous challenges for those with inadequate capacities due to the large volume and hazardous constituents created, specifically in developing countries. This paper aims to report the findings of post-disaster waste management strategies and challenges identified in Sri Lanka. Data was gathered through interviews with government and non-government organisations at national and local level. The lack of an established hierarchy and single point of responsibility, mandatory and enforceable rules and regulations; inadequate capacity and funds, and lack of communication and coordination were identified as gaps in post-disaster waste management. This enabled the identification of post-disaster waste management strategies, highlighting gaps that need to be addressed for effective C&D debris management for Sri Lanka's future resilience.